Reading Literacy and Numeracy Assistance for Elementary School Students in West Ceram District - Adam Latuconsina; Dewinofrita Dewinofrita; Sarfa Wasahua; Kapraja Sangadji; Satia Latuconsina; Nur Faizah Latuconsina; Enggal Mursalin; Susi Hardila Latuconsina; Nurul Latuconsin (IAIN AMBON, 2021)
Abstract. Community Service Activities (PKM) in the form of mentoring are aimed at, 1) increasing students' reading and numeracy literacy skills, 2) increasing learning motivation and competence in facing face-to-face learning. The methods used during the training were lectures, interactive discussions and mentoring by experts. The results of this PkM activity are, 1) 8 (eight) already have an average literacy score greater than 60, while 2 (two) other schools are still below a score of 60; 2) 8 (eight) schools already have an average numeracy score above 60, while 2 (two) schools are below a score of 60.